2020
DOI: 10.1111/xen.12632
|View full text |Cite
|
Sign up to set email alerts
|

Immunological response in cynomolgus macaques to porcine α‐1,3 galactosyltransferase knockout viable skin xenotransplants—A pre‐clinical study

Abstract: Background: Allogeneic skin recovered from human deceased donors (HDD) has been a mainstay interim treatment for severe burns, but unfortunately risk of infectious disease and availability limitations exist. Genetically engineered ɑ-1,3 galactosyltransferase knockout (GalT-KO) porcine source animals for viable skin xenotransplants may provide a promising clinical alternative. Methods: Four cynomolgus macaque recipients received full-thickness surgical wounds to model the defects arising from excision of full-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 57 publications
2
8
1
Order By: Relevance
“…Previous testing of skin xenotransplants had demonstrated that porcine cells were detectable at the graft site but as found here, this did not extend to the peripheral circulation [70], which did not appear to be the case for this study. Given the lack of detection here and the immunological responses shown, this supports the expectation that the porcine transplant is fully replaced and repopulated by the host cells.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Previous testing of skin xenotransplants had demonstrated that porcine cells were detectable at the graft site but as found here, this did not extend to the peripheral circulation [70], which did not appear to be the case for this study. Given the lack of detection here and the immunological responses shown, this supports the expectation that the porcine transplant is fully replaced and repopulated by the host cells.…”
Section: Discussioncontrasting
confidence: 65%
“…Due to the large number of surgeries, ve sciatic nerve segments were transplanted fresh one to two days after donor harvesting while the remaining ve were cryopreserved and subsequently thawed for transplantation over two days the week following based on Holzer et. al., 2020 [70]. Cryopreservation of xenogeneic skin transplants has been shown to be safe and effective for up to seven years [75], demonstrating no signi cant or meaningful differences between fresh and frozen transplants.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Lymphocytes in the surrounding tissue are indicative of a low level, long-term immune response consistent with porcine tissue clearance and nerve remodeling observed at the transplantation site [24]. detectable at the graft site [15]. In this study, qPCR for the porcine centromere was negative.…”
Section: Immunogenicitysupporting
confidence: 71%
“…Due to the large number of surgeries, five sciatic nerve segments were transplanted fresh one to two days after donor harvesting while the remaining five were cryopreserved and subsequently thawed for transplantation over two days the week following based on Holzer et. al., 2020 [15].…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…The advent of cutting‐edge tools and techniques to genetically engineer donor animals is a significant advantage and such technologies such as CRISPR has allowed researchers to produce the α1,3‐galactosyltransferase (GGTA1) gene knockout (GALKO) pig in order to mitigate hyperacute rejection in the xenotransplantation setting 23 . To investigate the potential for porcine xenograft skin replacement and to confirm the safety, tolerability, and recipient's immunological response from GALKO pigs Holzer et al 24 investigated the effectiveness of skin xenotransplants in a non‐human primate model (NHP). The cynomolgus macaque recipients received full‐thickness surgical wounds to model the defects arising from excision of full‐thickness burn injury and were subsequently treated with biologically active skin xenotransplants derived from GALKO pigs and monitored for 30 days.…”
Section: Modification Of the Donor Including α‐13 Galactosyltransferasementioning
confidence: 99%